PENGARUH KEAMANAN, KEPERCAYAAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN DI APLIKASI SHOPEE (STUDI KASUS MASYARAKAT KOTA TARAKAN) - Ferawati Usman; Nursia Nursia; Suryaningsih Suryaningsih (Cross-border, 2023)
Electronic commerce or e-commerce is now a business platform that has very good opportunities to do business for business people in the online trading industry. Indonesia is the country with the highest e-commerce adoption rate in 2019. As many as 90 percent of users aged 19-45 years apply e-commerce as a medium for online transactions, both purchasing products and services (Husain, 2020) . Shopee is a marketplace that has just emerged compared to several other marketplaces that were released earlier such as Tokopedia, which has existed since 2009. Now, Shopee is one of the marketplaces that has successfully penetrated into the most popular marketplace category in Indonesia (Databoks, 2020). This study describes the influence of security, trust, convenience on purchasing decisions in the shopee application for the people of Tarakan city. The population of this study was those who had used the shopee application in shopping with the age category of 17 years, men and women with a sample of 200. Data analysis used multiple linear regression and hypothesis testing. The results of the study show that trust, convenience, and security have a positive and significant effect on purchasing decisions. This shows the perception that consumer trust has an influence on purchasing decisions. Shopee builds consumer trust through improving the quality of services with the latest attractive features such as free shipping which promises consumers to make purchase transactions and provides guarantees of security ranging from safe transactions to convenience in interacting with sellers in the Shopee application.